Smart Water Leakage Monitoring System - Manisegaran, Danarajan; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2022)
The main aim of this project is to develop an intelligent monitoring system for water leakage detection in the water distribution system. Leakage constitutes a major loss of drinking water when supplied through pipeline systems. Introducing automated leakage detection systems would save a huge amount of water globally. Water leak detection by means of a simple embedded system aids water conservation in a cost-effective way. It focuses mainly on two parts: The first part is a real-time water leakage detection system using a flow meter. The second is the controlling part; it uses Arduino to control the solenoid valve and alert the owner using the Blynk application with the aid of a Wi-Fi module. The system is made up of basic components: flow rate sensors, a Wi-Fi module, Arduino, and relays to control the device. The result of using the proposed system is improving the efficiency of operation, reducing delay time and cost of maintenance pipelines after leakage detection.